Beauty in decay - Brakefeld, Jennifer L., author; Sullivan, Patrice, advisor; Osborne, Erika, advisor; Simons, Stephen, committee member; McKee, Patrick, committee member (Colorado State University. Libraries, 2014)
Industrial Agricultural complexes offer an aesthetic beauty in the decay of its materials and structures. American interest in agriculture as an investment in domestic self-reliance has waned over time leaving behind gigantic structures that are left to deteriorate without upkeep. The lack of upkeep causes a physical deterioration of the structures and the materials. My work exposes the beauty in this deterioration though the use of the formal elements of painting. Color, texture, form and light are the elements used for the execution of my paintings. Canvas size also plays a key role in my work as it places the subject matter on a historically relevant scale in a similar fashion to the painting Burial at Ornan by Gustav Courbet.
Keywords: agriculture; color; industry; painting; regionalism; texture